Perancangan Sistem Informasi Perizinan Guru dan Siswa di SMA Terpadu Riyadlul Ulum Tasikmalaya - Bima Andika Putera; Otong Rukmana (Bandung Conference Series: Industrial Engineering Science, 2023)
Abstract. Riyadlul Ulum Integrated Senior High School is an integrated boarding school-based school, by combining the State Education curriculum, Salafi Islamic Boarding School curriculum and Gontor Islamic Boarding School curriculum. One of the school administrators who really need the use of information technology is the administrator in the field of KMI (Kulliyatul Muallimiatul Islamiyah) or can be called the academic field at this school. This field is responsible for everything that happens in the KBM process. One form of service provided by the academic field is licensing. Licensing is a service for teachers and students who cannot take KBM. Licensing services have several stages in the application process. Licensing is divided into 2 categories, namely activity permits and sick permits. In the process of applying for an activity permit, teachers are required to ask for a permit from the picket teacher on duty and then ask the principal for a signature as validation, but for sick permits the teacher can ask for permission from home by contacting the picket teacher and the picket teacher will take care of the permit. Unlike the case for student licensing, students who want to apply for permission are simply represented by the class leader who applies for permission to the picket teacher before the first hour of KBM starts. The website is one of the containers that can be used as a source of information and proportional school data storage. Keywords: Information system, Prototype method, teacher and student permission. Abstrak. SMA Terpadu Riyadlul Ulum merupakan sekolah yang berbasis pondok pesantren terpadu, dengan memadukan kurikulum Pendidikan Negeri, kurikulum Pesantren Salafi dan kurikulum Pesantren Gontor. Salah satu pengurus sekolah yang sangat membutuhkan pemanfaatan teknologi informasi adalah pengurus di bidang KMI (Kulliyatul Muallimiatul Islamiyah) atau dapat disebut bidang akademik pada sekolah ini. Bidang ini bertanggung jawab atas segala hal yang terjadi pada proses KBM. Salah satu bentuk pelayanan yang diberikan oleh bidang akademik adalah perizinan. Perizinan merupakan sebuah layanan bagi para guru dan siswa yang tidak dapat mengikuti KBM. Layanan perizinan memiliki beberapa tahap dalam proses pengajuannya. Perizinan dibagi menjadi 2 kategori yaitu perizinan kegiatan dan perizinan sakit. Dalam proses pengajuan perizinan kegiatan, guru diharuskan untuk meminta surat izin kepada guru piket yang bertugas kemudian meminta tanda tangan kepada kepala sekolah sebagai validasi, namun untuk perizinan sakit guru dapat meminta izin dari rumah dengan menghubungi guru piket lalu guru piket tersebut yang akan mengurus perizinannya. Berbeda halnya pada perizinan siswa, siswa yang ingin mengajukan izin cukup diwakilkan ketua kelas yang mengajukan izin kepada guru piket sebelum jam pertama KBM dimulai. Website adalah salah satu wadah yang dapat dipakai sebagai sumber informasi dan penyimpanan data sekolah yang proporsional. Kata Kunci: Sistem Informasi, Metode Prototype, Perizinan Guru dan Siswa.